Multidimensional poverty status of rural households in Nigeria-does family planning have any effect? (2017)
Purpose – The purpose of this paper is to examine the factors influencing the use of family planning and its link with multidimensional poverty in rural Nigeria. Design/methodology/approach – The Alkire and Foster measure of poverty as well as the Logistic and Probit models were used to identify the factors influencing the use of family planning and its effect on the multidimensional poverty status of rural households in Nigeria. Findings – The results indicate that 31.1 percent of rural households were poor with deprivations in health and education contributing the most to multidimensional poverty. The low use of contraception was closely linked to low level of literacy, lack of awareness of the different methods and high levels of poverty. The use of contraception reduced the level of poverty in the household. Social implications – The intensity of poverty should be considered in the design of policies and programs. The wide and proper use of family planning is a sine qua non for any significant reduction in poverty. Potent and assertive family planning programs by government could be achieved through public-private sector partnership and assistance of international development partners. Originality/value – This paper attempts to bridge the knowledge gap in the empirical literature on the link between multidimensional poverty and family planning. In particular`, its application to the rural context, often characterized by high rate of poverty and unmet needs for family planning employing nationally representative data is of immense value for social policy.